(untitled) (The Research of Medical Science Review, 2025)
The emergence of immunotherapy has revolutionized the landscape of cancer treatment in veterinary oncology, offering promising new avenues for managing tumors in companion animals. This study presents a comprehensive analysis of current immunotherapeutic strategies, including immune checkpoint inhibitors, cancer vaccines, adoptive T-cell therapies, and monoclonal antibodies, highlighting their mechanisms, clinical applications, and outcomes. Through a structured review of preclinical data and ongoing clinical trials, we found that checkpoint inhibitors targeting PD-1 and CTLA-4 achieved tumor regression rates of up to 45% in canine models, while cancer vaccines demonstrated prolonged survival and disease stabilization across canine and feline patients. Tumor specific immunity can also be enhanced by treatments like monoclonal antibodies as well as adoptive T cell therapy which are, however, still in the experimental phase. Several patterns of treatment resistance were identified that are associated with the tumor microenvironment, including T-regulatory cells and cytokine balance, hypoxia, and other factors. We also found that combining immunotherapy with chemotherapy or radiation enhanced therapeutic effects and suppressed resistance factors. Also, new noninvasive imaging techniques such as immuno-PET and metabolic response criteria like imPERCIST5 criteria were also reported to improve the diagnostic accuracy of the disease and also the therapeutic management. These observations emphasize the importance of using biomarkers in order to individualize immunotherapy protocols and substantiate the inclusion of immunotherapy in the standard treatment regimens of veterinary oncology. All in all, this work strengthens the prospect of translating human cancer immunotherapy models and promises the development of exact, applied, and tailored cancer therapies for companion animals.